All Days 2010
DOI: 10.2118/135627-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Oil Recovery From Siliceous Shale by Miscible CO2 Injection

Abstract: This work presents the results of tests using a low permeability (1.3 mD), medium porosity (34%) siliceous shale reservoir core sample initially saturated with oil followed by CO2 injection at miscible conditions. The tests had 3 primary flow conditions that replicate aspects of expected field conditions: (i) countercurrent exchange of carbon dioxide from fracture to matrix with consequent production of oil (ii) cocurrent exchange of carbon dioxide from fracture to matrix with oil production at the downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Shyeh-Yung (Shyeh-Yung, 1991) concluded that two mechanisms of CO 2 EOR were low interfacial tension (IFT) displacement and extraction of oil components, and the latter dominated after CO 2 breakthrough. Vega B. et al (Vega, O'Brien, and Kovscek, 2010) conducted the miscible injection of CO 2 into siliceous shale. CO 2 injection under countercurrent (diffusion-like) conditions achieved 54% recovery of the OOIP and subsequent (displacement-like) cocurrent process yielded 39% recovery of the OOIP with a total 93% oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Shyeh-Yung (Shyeh-Yung, 1991) concluded that two mechanisms of CO 2 EOR were low interfacial tension (IFT) displacement and extraction of oil components, and the latter dominated after CO 2 breakthrough. Vega B. et al (Vega, O'Brien, and Kovscek, 2010) conducted the miscible injection of CO 2 into siliceous shale. CO 2 injection under countercurrent (diffusion-like) conditions achieved 54% recovery of the OOIP and subsequent (displacement-like) cocurrent process yielded 39% recovery of the OOIP with a total 93% oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Miscible CO 2 injection increased recovery from 6.02% obtained under primary production to 21.58% of OOIP. Vega et al (2010) studied miscible CO 2 injection into siliceous shale with 1.3 md permeability and 34% porosity. Experimental and simulation results together with computed tomography image analysis revealed CO 2 was able to penetrate from the fracture to the matrix and recover almost all the oil.…”
Section: Introductionmentioning
confidence: 99%
“…Different investigators have demonstrated the efficiency of molecular diffusion in fractured reservoirs (e.g. da Silva and Belery, 1989;Hu and Whitson, 1991;Darvish et al, 2006;Hoteit and Firoozabadi, 2009;Vega et al, 2010;Jamili et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…da Silva and Belery, 1989;Coats, 1989;Darvish et al, 2006;Vega et al, 2010;Jamili et al, 2010), multicomponent molecular diffusion is modeled using a classical Fick's law approach with effective diffusion coefficients. This means the diffusion flux of each component will always be in the opposite direction of its concentration gradient.…”
Section: Introductionmentioning
confidence: 99%